THE ROLE OF EXCHANGE PROPORTIONS IN THE INFLATION AND ECONOMIC CRISES - P. V. Ushanov (Стратегические решения и риск-менеджмент)
The article terminates the author's series of publications on the impact of system of stereotypes of behaviour – "success formula" - on the development of phases of the life cycle of the socio-economic systems [7-11]. The author argues in favor of the view that lifecycle of any object of management is a complex spiral consisting of 10 phases, each of which, in turn, can be regarded as a separate life cycle. Because of the stereotypes of behaviour, prevailing during previous lifecycle phases, a change of lifecycle phases often leads to a crisis and is accompanied by painful correction of exchange proportions. The author motivates his conclusion that the modern economic crisis is caused by the distortion of exchange proportions. The indexes of changes in exchange proportions are proposed to use as an indicator of stability of the world market. Proposals on overcoming the crisis are made.